Motivasi Berkunjung ke Posyandu dalam Rangka Kesehatan Bayi dan Anak di Kelurahan Denai Kota Medan - Maswita Maswita (Keguruan, 2022)
Mother's motivation is one of the supporting factors and indispensable in monitoring the growth of infants and toddlers. The purpose of this study is to describe the factors that motivate a mother why she needs to visit the Posyandu or not. This study used a phenomenological qualitative method. Data were collected using semi-structured interview technique. The results showed that there were three categories of responses, namely (1) two families did not use Posyandu as health facilities and infrastructure due to the habitual orientation of the previous generation; (2) two families did not go to Posyandu because they felt that their family was healthy; (3) one family worried that immunizing their child will get then into fever and illness. For the health of mothers and children, some informants simply breastfeeding and eat a complete meal and carry out the inherited habits from their parents. Meanwhile, the families who visited the Posyandu were because the four families who became informants said that the Posyandu was very useful for children's growth and development and one family visited the Posyandu because there were souvenirs such as sugar, green beans, as well as for children's health.